Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/om300813t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterizations of Bismuth-Bridged Triiridium Carbonyl Complexes Containing Germyl/Germylene and Stannyl/Stannylene Ligands

Abstract: The reaction of Ir3(CO)9(μ3-Bi) with Ph3GeH yielded the compound Ir3(CO)6(GePh3)3(μ3-Bi)­(μ-H)3 (1). When 1 was heated to reflux in hexane, it was transformed into the compound Ir3(CO)6(μ-GePh2)3(μ3-Bi) (2), which contains three bridging GePh2 ligands by loss of 3 equiv of benzene. The reaction of Ir3(CO)9(μ3-Bi) with Ph3SnH yielded the compounds Ir3(CO)6(SnPh3)3(μ3-Bi)­(μ-H)3 (3) and Ir3(CO)6(μ-SnPh2)3(μ3-Bi) (4), respectively. Compounds 1–4 were characterized crystallographically. Compounds 1 and 3 each have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…In addition, compound 3 contains two SnPh 3 ligands that occupy equatorial coordination sites, one on each of the two Ir(CO) 2 groups. The Ir−Sn bond distances are similar in length, Ir3−Sn1 = 2.6415(18) Å, Ir2−Sn2 = 2.6413 (19) Å, and are similar to those found in the compounds Ir 3 (CO) 6 (SnPh 3 ) 3 -(μ-H) 3 (μ 3 -Bi) 5 and Ir 3 (CO) 6 (SnPh 3 ) 3 (μ-SnPh 2 ) 3 . 27 There is a hydride ligand bridging the Ir−Ir bond between the two tinsubstituted iridium atoms.…”
Section: Inorganic Chemistrysupporting
confidence: 74%
See 2 more Smart Citations
“…In addition, compound 3 contains two SnPh 3 ligands that occupy equatorial coordination sites, one on each of the two Ir(CO) 2 groups. The Ir−Sn bond distances are similar in length, Ir3−Sn1 = 2.6415(18) Å, Ir2−Sn2 = 2.6413 (19) Å, and are similar to those found in the compounds Ir 3 (CO) 6 (SnPh 3 ) 3 -(μ-H) 3 (μ 3 -Bi) 5 and Ir 3 (CO) 6 (SnPh 3 ) 3 (μ-SnPh 2 ) 3 . 27 There is a hydride ligand bridging the Ir−Ir bond between the two tinsubstituted iridium atoms.…”
Section: Inorganic Chemistrysupporting
confidence: 74%
“…Similar dynamical activity was observed for the very similar compound Ir 3 (CO) 6 (GePh 3 ) 3 -(μ-H) 3 (μ 3 -Bi). 5 The Ir−Ir bond distances in 3 are similar to those found in 2, Ir1−Ir3 = 2.8211(14) Å and Ir1−Ir2 = 2.8221(13) Å, except for the hydride-bridged Ir−Ir bond, Ir2−Ir3 = 2.9098(14) Å, When compound 2 was allowed to react with HSnPh 3 in the presence of H 2 O for 24 h at 25°C, compound 3 was obtained in 24% yield, together with the new compound 4 in 13% yield. It was subsequently shown that compound 4 can be obtained in an even better yield (24%) directly by the reaction of 3 with H 2 O.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…20 We have recently prepared a number of iridium-bismuth complexes containing germanium and tin ligands from complex 1 by reactions with HGePh 3 and HSnPh 3 . 21 We have now found that 1 reacts with BiPh 3 to yield the new higher nuclearity complex Ir 5 (CO) 10 (μ 3 -Bi) 2 (μ 4 -Bi), 2 in high yield (91%), see Scheme 1. Compound 2 was characterized crystallographically by singlecrystal X-ray diffraction and an ORTEP diagram of its molecular structure is shown in Figure 2.…”
mentioning
confidence: 89%
“…( 1 ) There are very few examples of iridium-bismuth carbonyl cluster complexes [3][4][5]. We have previously shown that the compound Ir 3 (CO) 9 (µ 3 -Bi), 1 [3] can be converted into the higher nuclearity complex Ir 5 (CO) 10 (µ 3 -Bi) 2 (µ 4 -Bi) by reaction with BiPh 3 , eq.…”
Section: Introductionmentioning
confidence: 99%